Prediction and Diagnosis of Poor Ovarian Response: The dilemma - Badawy, Ahmed; Wageah, Alaa; EL-Gharib, Mohamed; Osman, Ezz Eldin (Journal of Reproduction & Infertility, 2011)
Failure to respond adequately to standard protocols and to recruit adequate follicles is called ‘poor response’. This results in decreased oocyte production, cycle cancellation and, overall, is associated with a significantly diminished probability of pregnancy. It has been shown that ovarian reserve tests, such as basal FSH, antimullarian hormone (AMH), inhibin B, basal estradiol, antral follicular count (AFC), ovarian volume, ovarian vascular ﬂow, ovarian biopsy and multivariate prediction models, have little clinical value in the prediction of a poor response. Although recent evidence points that AMH and AFC may be better than other testsbut they still continue to be used and form the basis for the exclusion of women from fertility treatments. Despite the rigorous efforts made in this regard, a test that could reliably predict poor ovarian response in all clients that undergo IVF is currently lacking.
Keywords: Controlled ovarian hyperstimulation; Female infertility; Ovarian failure; Poor ovarian response